Human-Computer Interaction. Towards Mobile and Intelligent Interaction Environments 14th International Conference, HCI International 2011, Orlando, FL, USA, July 9-14, 2011, Proceedings, Part III - Jacko, Julie A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This four-volume set LNCS 6761-6764 constitutes the refereed proceedings of the 14th International Conference on Human-Computer Interaction, HCII 2011, held in Orlando, FL, USA in July 2011, jointly with 8 other thematically similar conferences. The revised papers presented were carefully reviewed and selected from numerous submissions. The papers accepted for presentation thoroughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The papers of this volume are organized in topical sections on mobile interaction, interaction in intelligent environments, orientation and navigation, in-vehicle interaction, social and environmental issues in HCI, and emotions in HCI.
Keywords: Computer science; Computer Communication Networks; Information storage and retrieval systems; Information systems; Multimedia systems; Computer vision; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl.Internet).; Multimedia Information Systems; Information Storage and Retrieval; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Communication Networks